PENGARUH KOMPETENSI GURU, BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA GURU SMK YAPIM SUMATERA UTARA - Suharti,S.Pd.Gr -; Edi Siregar; Yosi Stefhani (Pasca Sarjana Universitas Satya Negara Indonesia, 2025)
ABSTRACT This study aims to analyze the direct and indirect effects of teacher competence, organizational culture, and compensation on teacher performance at SMK YAPIM Taruna North Sumatra. The study uses a quantitative method with a census approach to all teachers as respondents, and data is collected through questionnaires. Path analysis is used to test the relationship between variables with the help of statistical software. The results of the study indicate that teacher competence, organizational culture, and compensation have a positive and significant effect on teacher performance, as reflected in increased loyalty and quality of service to students. The novelty of this study lies in the integration of the three main variables into a single analytical model that simultaneously measures their impact on teacher performance in a vocational school environment, which has not been comprehensively studied in a similar context. These findings have implications for school administrators to strengthen strategies for improving teacher performance through competency development, strengthening a conducive organizational culture, and providing fair and equitable compensation. Kata kunci: Teacher competence, organizational culture, compensation and teacher performance